(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article analyzes the impact of macroeconomic and institutional factors on interbank competition in the banking sector of Uzbekistan. The study applies a panel Fixed Effects regression model for 2016–2025 to empirically assess the impact of eight competition determinants on the Lerner index. Based on the conducted research, the author formulates conclusions and provides practical recommendations.